Survei kebugaran jasmani siswa di Sekolah Dasar Negeri Sumbersari III Kota Malang - Faizal Handoko Putra; Ari Wibowo Kurniawan (Program Studi Pendidikan Jasmani Kesehatan dan Rekreasi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Islam 45, 2023)
Physical fitness is one of the crucial aspects of daily activities. Having a fit physical fitness can help students be better prepared to follow the learning process at school. This study aims to see the level of physical fitness in students of Sumbersari III State Elementary School Malang City. For this study using quantitative descriptive method using survey design. For the experimental subjects in this study, namely students of Sumbersari III State Elementary School in Malang City with a population of 83 students and 43 students as research samples. The data obtained based on the calculation of the TKJI test results processed by manual calculation, shows that students who have physical fitness on a very good size are 0 students, then students who have physical fitness on a good size are 0 students, then students who have physical fitness on a medium size are 3 students, then students who have physical fitness on a lesser size are 22 students, while students, who have physical fitness on a very poor size are 18 students. Therefore, the physical fitness of students at Sumbersari III State Elementary School in Malang City is classified as having a poor level of physical fitness.